Report on Gender Equality (HER+) Initiative training workshop on gender-responsive and nutrition-sensitive agriculture Ethiopia - Yami, Mastewal; Ketema, Dessalegn Molla; Nchanji, Eileen; Lutomia, Cosmas Kweyu; Ahmed, Abel; Zewde, Yidnekachew; Jaleta, Gemechis; Asrat, Alemayehu; Hailu, Shimelis; Biruk, Fitsum (2023)
The Gender Equality Initiative (HER+) conducts innovative gender and social science research to develop actionable solutions to enhance climate resilience and empowerment of women in Africa and Asia. As one-size-fits-all solutions do not exist, HER+ identifies and develops diverse scenarios for co-creation of bundling socio-technical innovations. In Ethiopia, the initiative is closely working with the Veggies for Planet and People (V4P&P) project implemented by the World Vegetable Center and SNV (Netherlands Development Organisation) that aims to improve vegetable production, consumption and marketing. The project focuses on youth and women job creation while safeguarding the environment through regenerative agricultural practices and Vegetable Business Networks (VBNs). The HER+ program activities support the WorldVeg’s intervention through women’s empowerment (not excluding men and youths) in vegetable production by harnessing the potential of socio-technical innovation bundling and in addressing gender inequalities and improve nutrition outcomes through nutrition-sensitive interventions. By integrating technology, social innovation, and gender-responsive approaches, this program aims to create an enabling environment for women, men and youths to take an active role in decision-making, resource allocation, and nutrition practices.